Estado, cooperação e direitos humanos: a possibilidade de harmonização no cumprimento das sentenças da Corte Interamericana de Direitos Humanos - Anjos, Priscila Caneparo dos (2015)
This study aims to analyze the implementation of judgments of the Inter-American Court of Human Rights by States which recognized its contentious jurisdiction. Thus aims at gradual improvement in human rights conditions in those locations by developing proposals to harmonize legislations regarding the implementation of nonfinancial terms of inter-American sentences minted in international cooperation. The importance of this research rests on high rates of non-compliance of its indictments, especially those obligations of doing and not doing imposed on States. Therefore, in a sharing sovereignty reality, a viable direction for this scenario is the use of cooperation tools. By seeing that only Peru and Colombia have these laws and they not complied them satisfactorily the first proposal is based on the implementation and improvement of these regulations, applying them successfully in all States that are part of the compulsory jurisdiction of the Court; as an alternative, the thesis alluded to the United Kingdom´s system, which greatly contributes to the effective enjoyment of human rights. For the correct understanding, it was discussed about the State devices: social formations, its historical and elements, the influence of the globalization, the consequent of the sharing sovereignty and the emergency of international organizations. Furthermore, the study examined the international cooperation and its utility for the guarantee of effectiveness of human rights, by analyzing its concepts, principles and its practical application nowadays. Human rights were also the foundation of this thesis, as well as their structural apparatus and its consequent international protection, reached the study of the inter-American system for the protection of human rights. Finally, the thesis looking at each of the States that recognized the contentious jurisdiction of the Inter- American Court to understand each internal milestone about the protection of human rights and their predictions of the implementation of international sentences. Thus, it was possible to understand local necessities and connect them to the possibility of harmonization of legislations by using cooperation tools. The study concluded that the effectiveness of human rights sentenced by Inter-American Court would be assured, at least, legally